Profile of sexual function using Female Sexual Function Index (FSFI) in post-menopausal women in Geriatric Clinic, Dr Soetomo Hospital, Surabaya - Miftha Hurrahmi; Eighty Mardiyan K; Azami Denas A; Sulistiawati Sulistiawati (Universitas Airlangga, 2017)
Objectives: to describe the profile of sexual function in post-menopausal women at Geriatric Clinic, Dr. Soetomo Hospital, Surabaya in May 2016 and to determine the factors of sexual dysfunction in 6 sexual domains.Materials and Methods: a descriptive study using survey to obtain data on the examined variables. Population in this study was all post-menopausal women at Geriatric Clinic of Dr. Soetomo Hospital, Surabaya, in May 2016. Data were obtained using Female Sexual Function Index (FSFI) questionnaire.Results: Total population in this study was 160 patients. The number of samples who met inclusion criteria were 90 patients, but only 37 were willing to participate. The prevalence of samples who were still active in sexual intercourse was 29.7%. Based on 6 sexual domains, the prevalence of the lack of desire was 48.6%, lack of arousal was 75.7%, lack of lubrication was 73%, lack of orgasm was 73%, lack of satisfaction was 73% and pain was 70.3%. The assessment of sexual function found that 78.4% of the samples were sexually dysfunctional.Conclusion: The high prevalence (78.4%) of sexual dysfunction in post-menopausal woman was caused by dysfunction in sexual domain.